Studi Perbandingan Antara Memori DRAM dan Memori SRAM Dalam Sistem Keamanan Komputer - Widya Dwi Agustin; A. Dhyta Maulana; Dede Wirta; Didik Aribowo (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2023)
The ever-evolving digital world has made computer security an increasingly important and urgent issue. Computer security refers to a set of practices, policies and technologies designed to protect computer systems, networks and data from threats such as cyber attacks, data theft and software damage. The purpose of this research is to compare DRAM memory and SRAM memory in computer security systems. This research uses the library research method, which is the collection of information or scientific papers related to literature reviews that are literature. the selection between DRAM and SRAM must consider physical and software security needs, as well as system performance and power consumption.